Text recognition from images mobile application - Phua, Melvin (Nanyang Technological University, 2020)
Recognizing text from images with computers has been made possible through the advancement of Computer Vision or a more specific term relevant to this project, OCR (Optical Character Recognition). It became especially popular in the past decade and has been widely used in applications such as Google Translate. Being an existing technology, OCR is widely supported and has reached new levels of accuracy resulting in further applications of how the text data collected can be used. Apart from its OCR capability, this project extends its function to extract keywords which could be used for a variety of purposes such as archiving, sorting and managing. The use case possibilities are endless and ultimately, this project hopes to become an essential application for end users to use in their daily lifestyle.